Formation of chitosan beads and lactic acid production by chitosan-immobilised lactobacillus sp - Rusmin, Ruhaida; Zakaria, Zainoha (SSM International Publication, India, 2007)

(untitled)
Chitosan is a biopolymer derived by deacetylation of chitin and has special properties such as hydrophilicity, biocompatibility, and is biodegradable. In this study, chitin was obtained from Tiger prawn waste through fermentation process. The chitin was then deacetylated to form chitosan with various degrees of deacetylation. Chitosan beads were prepared by dropping chitosan solution into sodium pyrophosphate which act as gelling agent. Several parameters such as degree of deacetylation (DD), concentration of chitosan solution, pH and concentration of sodium pyrophosphate solution were studied to determine their effect towards the formation and porosity of chitosan beads. High DD, high concentration of chitosan, and high pH of sodium pyrophosphate were found important to facilitate the formation of spherical shaped chitosan beads which is also supported by SEM and IR analyses. The fermentation of glucose by chitosan-immobilised Lactobacillus sp. produced 535 x 10-3 g/L of lactic acid over a period of three days. Upon recycling, chitosan-immobilised cells were able to maintain its shape until the third cycle.